Larch Tree Rings as a Tool for Reconstructing 20th Century Central European Atmospheric Mercury Trends - Navrátil, Tomáš; Nováková, Tereza; Shanley, James B; Rohovec, Jan; Matoušková, Šárka; Vaňková, Maria; Norton, Stephen A (Environmental science & technology, 2018)
We propose the tree rings of European Larch ( Larix decidua) as a widely available and reliable geochemical archive of local and regional changes in atmospheric mercury (Hg). Mean Hg concentrations in larch tree rings from 8 background sites across the Czech Republic ranged from 2.2 to 4.8 μg kg-1; the maximum concentrations occurred in the period 1951-1970. At 3 sites impacted by Hg-emission sources [gold amalgamation processing, caustic soda production, and lead (Pb) ore smelting] mean larch tree ring Hg concentrations were significantly elevated relative to background sites. Changes in larch tree ring Hg concentrations were temporally coherent with known activities at the sites that would alter Hg emissions; the nearly simultaneous response in tree rings indicated little or no translocation of Hg within the larch bole. Based on the present-day atmospheric Hg concentration of 1.63 ng m-3 at the intensively monitored Czech Global Mercury Observation System site and the most recent mean tree ring Hg concentration of 2.8 μg kg-1 in co-located larch trees, we developed a simple distribution model of Hg between the atmosphere and larch tree rings. We applied the model using observed changes of Hg in larch tree rings from the countrywide background sites to reconstruct past atmospheric Hg concentrations in central Europe. Modeled Hg concentrations were in agreement with annual means from the European Monitoring and Evaluation Programme observatories.
Keywords: zlato; Česká republika; Larix; rtuť; Mercury; Gold; Europe; Evropa; Czech Republic; modřín; Environmental Monitoring; monitorování životního prostředí